Synthesis and Characterization Number of new Dinuclear Complexes of Mn(II),Co(II),Ni(II), Cu(IIDerived from reaction of (6-bromo-2-aminothazole with 1-chloro-2-(2-Chloroethoxy)Ethan (Journal of the College of Basic Education, 2022)
Research includes the preparation and diagnosis of a number of new complexes of manganese (ll), cobalt (ll), nickel (ll) and copper (ll) and zinc (ll) with ligand which was obtained by condensation of 2-Mole (6-bromo-2-Aminobenzothazole) with 1-mole of 1-chloro-2- (2-chloro ethoxy) for ligand (L) and then was reaction with bilateral metals parity above-mentioned solvent methanol, the proportion (ligand: metal) (2: 1) to obtain complexes that have a formula CI2 [M (L) (H2O) 2] was someone ligand record and complex by elemental analysis (CHN) and IR spectroscopy and spectral and electronic spectroscopy NMR and through the search results show that ligand exhibits binary age ligand behavior associated with All metallic ions through the nitrogen atoms linked in a ring Althazole .pent above studies that figure is expected to spatial complexes ligand record four-brightness distorted depending on the test results that were obtained.